2005
DOI: 10.14411/fp.2005.028
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and aspects of growth of a trypanosome transmitted by the marine leech Johanssonia arctica (Piscicolidae) from Northern Norway

Abstract: Abstract. The fish leech Johanssonia arctica (Johansson, 1898) was collected from king crabs Paralithodes camtschaticus (Tilesius, 1815) in Finnmark, N Norway, and allowed to feed on experimental fish hosts in the laboratory. This leech ingested blood from laboratory-reared cod (Gadus morhua) and halibut (Hippoglossus hippoglossus). Some experimental halibut acquired trypanosome infection, with parasitaemia between ca. 500 and 60,000 trypanosomes ml -1 . The trypanosomes were of variable size and measured 39-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…New primers were designed from these sequences (Table 2), and were used to amplify trypanosome SSU rDNA from samples of dried blood scraped off bloodsmears (with a sterile scalpel). These smears were unstained thin and thick blood/leucocyte smears of morphologically characterised trypanosomes from (i) wild cod (Table 1), (ii) smears from a cod experimentally infected with trypanosomes from the leech Calliobdella nodulifera (see Karlsbakk, 2004a) (DQ016614, DQ016615) and (iii) three halibut experimentally infected with trypanosomes from J. arctica (see Karlsbakk et al, 2005, halibut 1, 3-5) (DQ016616). The DNA templates were purified using the DNeasy protocol for animal tissues (Qiagen) according to the manufacturer instructions.…”
Section: Pcr and Sequence Datamentioning
confidence: 99%
See 3 more Smart Citations
“…New primers were designed from these sequences (Table 2), and were used to amplify trypanosome SSU rDNA from samples of dried blood scraped off bloodsmears (with a sterile scalpel). These smears were unstained thin and thick blood/leucocyte smears of morphologically characterised trypanosomes from (i) wild cod (Table 1), (ii) smears from a cod experimentally infected with trypanosomes from the leech Calliobdella nodulifera (see Karlsbakk, 2004a) (DQ016614, DQ016615) and (iii) three halibut experimentally infected with trypanosomes from J. arctica (see Karlsbakk et al, 2005, halibut 1, 3-5) (DQ016616). The DNA templates were purified using the DNeasy protocol for animal tissues (Qiagen) according to the manufacturer instructions.…”
Section: Pcr and Sequence Datamentioning
confidence: 99%
“…In addition, anterior cytoplasm tends to be finely granular, with series of small sometimes longitudinally arranged vacuoles. There are no detectable chromophilic granules, yellow pigment granules or refractive granules (sensu Laird, 1952;Khan, 1978;Karlsbakk et al, 2005).…”
Section: Pcr and Sequence Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Successful cross-transmission experiments have proven that particular trypanosome species are not restricted to the host species from which they were originally recovered (Lom 1973;Letch 1979;Woo and Black 1984), thus, refuting the host-specificity hypothesis. In addition, based on morphological criteria, Letch (1979) found that six fish species from different genus in British populations were infected with trypanosomes that were morphologically indistinguishable, and Karlsbakk et al (2005) found a trypanosome species transmitted by the marine leech from Northern Norway showing large disparities in morphology and aspects during different infection times. Moreover, most of the early descriptions are simple and inadequate according to current morphological standards (Smit et al 2004;Karbowiak et al 2005;Gu et al 2006bGu et al , 2007 and can hardly be used for a safe determination of species.…”
Section: Introductionmentioning
confidence: 99%